MENINGKATKAN KEMAMPUAN MENGENAL HURUF MELALUI PERMAINAN KARTU GAMBAR PADA ANAK USIA 4-5 TAHUN DI POS PAUD KENANGA KECAMATAN KAMPAR TIMUR KABUPATEN KAMPAR - Wirdanelis, Wirdanelis; Isjoni, Isjoni; Solfiah, Yeni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the increase in the ability to know the letters in children aged 4-5 years through card games or pictures in Pos ECD Kenanga East Kampar District Kampar district. This study is je nis studies using action research or (PTK) is conducted in two cycles. Each cycle consists of planning, action planning, observation / evaluation and reflection. Subject empirically n are children aged 4-5 years who totaled 15 children in early childhood Kenanga Pos. The research data obtained through observation and data analysis was done by using quantitative descriptive analysis. The results showed lower card game image can improve the ability to know the letters in children aged 4-5 years. It Dapa t be seen from the increase in the average percentage of the ability to know hurf in the first cycle of 51.7% which is the criterion begins to develop (MB) and increased by 45.7% in the second cycle to 77.4%, which is at criteria developed very well (BSB). So, the card game pictures d apat improve the ability recognize letters children aged 4-5 years in early childhood Kenanga Pos Kampar District Kampar Regency EastKeywords : Know the capabilities Letter, Image Card Games